PENGARUH PEMBERIAN KOSENTRASI ATONIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa. L) - Saverius Ervansius Mulyadi; l Made Sukerta; Komang Dean Ananda (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
This study is titled the effect of atonic concentration on the growth and yield of lettuce plants (Lactuca sativa. L). The purpose of this study is to find out the effect of atonic concentration treatment on the growth and yield of lettuce plants (Lactuca sativa. L). This study used Randomized Block Design (RBD). If the treatment has a real effect with bnt test level 5% to know the best effect of each treatment. The results of this study showed that the influence of atonic treatment has a very real effect on all parameters of lettuce plants observed. The effect of atonic concentration treatment of 5 cc/1 liter of water gives the result of other observed parameter values such as the highest plant height (A5 = 28.50 cm), the highest number of leaves (A5 = 35.50 strands), the total fresh weight of the plant (A5 = 16.57 g), and the dry weight of the total oven plant (A5 = 17.32 g). Based on the results obtained above, it can be concluded that the influence of atonic concentration on the growth and yield of lettuce plants (Lactuca sativa. L) gives a very noticeable influence on all the parameters of growth and yield of lettuce plants (Lactuca sativa. L).